(untitled) (Applied Biological Research, 2013)
The present study was based on the isolation, identification and biochemical characterization of Brucella species, the causal pathogen of brucellosis, from the samples taken from cattle and buffaloes in Punjab (India). Out of the 84 samples of vaginal mucus (35), foetal stomach content (31), foetal membranes (11) and uterine discharges (7), collected from aborted cattle (29) and buffaloes (55), 9 (10.7%) were positive through isolation. Of these 9 isolates, one isolate was typed as biotype 2, one as biotype 3 and seven as biotype 1. Prevalence of Brucella abortus through isolation in buffaloes and cattle was 10.9 and 10.3%, respectively. Maximum number of B. abortus isolations in cattle (25.9%) and buffaloes (41.2%) were obtained from the animals in age group of 4-6 years. All the brucellosis positive animals had history of abortion in 6-9th month of gestation. Antimicrobial sensitivity revealed that B. abortus was sensitive to doxycycline, oxytetracyclin, ampicillin, gentamicin, enrofloxacin, streptomycin, neomycin, chloramphenicol, norfloxacin and kanamycin but resistant to penicillin, cephalothin, cotrimoxazole and erythromycin.